KEPUASAN PASIEN DALAM PEMBERIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP MURNI TEGUH MEMORIAL HOSPITAL MEDAN - Sitorus, Herti; Mendrofa, Hendry Kiswanto (STIKes Murni Teguh, 2025)
Patient satisfaction is the result of the patient's assessment of health services by comparing what is expected in accordance with the reality of health services received. So that patient satisfaction at the hospital depends on how the services provided by the hospital. The objective of this study is to determine patient satisfaction in providing nursing care in the inpatient ward of the Murni Teguh Memorial Hospital. This study was a descriptive survey study. The population of this study were patients in the inpatient room of Murni Teguh Hospital Medan in July. The sampling technique in this study was Quota sampling, which was done by determining the number of research samples in advance, which was 60 people. The method of data collection with instruments on patient satisfaction uses a standardized questionnaire, namely the questionnaire gap model. The results showed that most of the patients said they were satisfied with the provision of nursing care as many as 52 (86.7%) and were not satisfied as many as 8 (13.3%). It is concluded that based on the results of the study showed that the better the provision of nursing care to patients, the level of patient satisfaction of nursing services will be better as well. It is recommended for further research to add variables such as factors related to patient satisfaction with the quality of nursing care.